Rounding up performance measures in German firms: Earnings cosmetics or earnings management on a larger scale? - Sebastian Lebert; Ulf Mohrmann; Ulrike Stefani (Journal of Business Finance & Accounting, 2021)
We use Benford's Law to provide evidence that German firms round up both their net income and earnings per share. We use the introduction of the euro to show that round earnings numbers are likely the result of earnings management. The incentive to round up comes from stakeholders' left-digit bias when processing the information in financial statements. Since round numbers are natural benchmarks, stakeholders perceive the performance metrics directly below such thresholds as abnormally lower. However, rounding up is objectionable only if it involves large-scale earnings management, but not in cases of negligible `earnings cosmetics'. Because the difference between the pre-managed and reported earnings is unobservable, we investigate whether the prevalence of rounding up coincides with specific levels of several earnings characteristics and proxies for audit quality. If the rounding up is cosmetic, then it should occur independently of these characteristics. In contrast, if firms use earnings management on a larger scale, then it might not be possible to simultaneously round up and achieve other objectives of earnings management. Our evidence is in line with substantial earnings management.
Keywords: 650; audit quality; Benford's Law; cognitive thresholds; earnings characteristics; earnings management; left-digit bias; rounding up